(untitled) (Advances in Applied Biological Research, 2025)
Background: One of the most frequent side effects of individuals with poorly managed type 2 diabetes is ulcers in their feet caused by diabetes. It is typically brought about by inadequate care for the feet, blood vessel disease with intrinsic nerve damage, or low blood sugar levels. It additionally serves as one of the leading causes of limb loss and bone disease within the leg. Objective: to assess Risk for Diabetic Foot Ulcer Associated with Type 2 Diabetes Mellitus Patients. Materials and Procedures: A descriptive study conducted at Al-Hilla Teaching Hospital to assess Risk for Diabetic Foot among Patients With Type 2 Diabetes Mellitus. Data collection take place from December 15, 2023, to February 30, 2024. The questionnaire’s validity was ensured through expert review Results: The high percentage %62 (50-60) years of age between (20-30) years, regarding the sex the result recorded 26(52.0) were female ,11(22.0) was post graduate regarding educational status, the result recorded 43(86.0) were married, related to occupation the result recorded 37 (74.0) were unemployed, and 13(26.0) were unemployed, related to residency the result recorded 31(62.0) were urban resident. Conclusions: highlights the significance of the study’s findings regarding diabetes foot risk among female, with old age play significant function in the progression of type two diabetic foot ulcers patient.